KAPASITAS PEMERINTAHAN DESA DALAM IMPLEMENTASI UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA DI JAWA TENGAH - Suharto Suharto (LP2M, 2018)
This article describes the Capacity of the Village Government in the framework of implementing the 2014 Law Number 6 concerning Villages which is very important in determining its success. In this study aims to determine the extent of the capacity of the Village Government in implementing the Village Law. Looking at the current condition of the Village which is very heterogeneous, both quantity, quality or capacity and even the potential of natural resources and human resources are very varied, so in the context of implementing the Village Law it needs to be addressed or concern us, especially academics. The problems in this study are: